Jump performance during a season in elite volleyball players - Piatti, M.; Ambrosi, E.; Dedda, G.; Omeljaniuk, R. J.; Turati, M.; Bigoni, M.; Gaddi, D. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The aim of this study was to measure and compare jump load and dynamic performance in elite volleyball athletes under varied conditions over an entire season of practices and games. Jump load and dynamic performance were compared among best jump height, mean jump height, as well as according to the number of jumps per game or practice session and the proportion of jumps higher than 50 cm relative to the total number of jumps in a practice or game. METHODS: Every jump performed by each of 12 players, in all practices and regular games (813 player-sessions in total), was measured by a particle accelerometer in accordance with a validated protocol (Vert, Fort Lauderdale, FL, USA). Data were collected and analyzed using STATA (SataCorp, College Station, TX, USA); the significance level for definition of confidence intervals was set to 95%, unless otherwise specified. Statistical analysis and comparison of means and proportions between groups was based on standard t-tests. RESULTS: Among player positions, the middle blocker consistently presented the greatest jump loads during the season; by comparison, the smallest jump loads were observed in the setter. CONCLUSIONS: Monitoring players` jump loads and performance using a simple accelerometer provides evidence which can be used to plan individual player activity, roster composition, the season calendar and furthermore increase knowledge to reduce over-training and recurrence of injuries.